2023
DOI: 10.3102/01623737221134528
|View full text |Cite
|
Sign up to set email alerts
|

What Schools Do Families Want (and Why)? Evidence on Revealed Preferences From New Orleans

Abstract: Prior research suggests that families prefer schools with higher test scores, shorter distances from home, and certain student demographics. We build on this using data from New Orleans, a context well suited to identification of parent preferences because of its deferred acceptance algorithm and extensive, standardized, and broadly accessible school information. This allows us to study revealed preferences for a richer set of characteristics. We find that families prefer schools with higher school value-added… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 56 publications
2
23
0
Order By: Relevance
“…Students may apply to any school in the city, and its extensive public transit system-which is subsidized for students-provides access to a large number of schools (Corcoran, 2018). However, prior studies have found that families have a strong preference for proximity when choosing schools (Glazerman & Dotter, 2017;Harris & Larsen, 2015;Hastings, Kane, & Staiger, 2006). Thus, we might expect residentially proximate families to make more similar choices, all else equal.…”
Section: The Role Of Choices School Supply and Preferences On Peer Co...mentioning
confidence: 99%
See 1 more Smart Citation
“…Students may apply to any school in the city, and its extensive public transit system-which is subsidized for students-provides access to a large number of schools (Corcoran, 2018). However, prior studies have found that families have a strong preference for proximity when choosing schools (Glazerman & Dotter, 2017;Harris & Larsen, 2015;Hastings, Kane, & Staiger, 2006). Thus, we might expect residentially proximate families to make more similar choices, all else equal.…”
Section: The Role Of Choices School Supply and Preferences On Peer Co...mentioning
confidence: 99%
“…On the demand side, prior research has found variation in school preferences by family background, with high-socioeconomic status (SES) parents and parents of higher-achieving students more likely to prioritize schools with high test scores than low-SES parents and parents of lower-achieving students (Abdulkadiroğlu et al, 2020;Glazerman & Dotter, 2017;Harris & Larsen, 2015;Hastings et al, 2006). Families also differ in preferences for the racial composition of schools (Bell, 2009;Billingham & Hunt, 2016;Goyette, 2008;Hailey, 2022b;Schneider & Buckley, 2002) and school safety (Hailey, 2022a).…”
Section: The Role Of Choices School Supply and Preferences On Peer Co...mentioning
confidence: 99%
“…The other is the expressed or stated preference approach, which focuses on what parents say about the school choice process, using interviews or survey data (Jabbar & Lenhoff, 2020). Studies from both approaches highlight some important considerations when choosing schools: families care about schools' achievement test scores or other measures of academic quality, distance to home, tuition, school's socioeconomic composition, among other factors (Altenhofen et al, 2016;Burgess et al, 2015;Cooper, 2005;Denice & Gross, 2016;Elacqua et al, 2006;Harris & Larsen, 2015;Hofflinger et al, 2020;Madero Cabib & Madero Cabib, 2012;Mandic et al, 2017;Maroulis et al, 2019). Both approaches are imperfect and necessarily simplify what is inherently a complex process (Cooper, 2005;Ellison & Aloe, 2018;Hastings & Weinstein, 2008;Hill & Scott, 2017;Jabbar & Lenhoff, 2020;Maroulis et al, 2010).…”
Section: School Choice Decision-making Processmentioning
confidence: 99%
“…Dominant school choice discourses position parents as rational actors who gather information about potential schools, evaluate that information, and effectively choose the highest performing options for their children (Blast & Walberg, 2004; Chubb & Moe, 1990). Though there is evidence that parents of all racial and socioeconomic backgrounds consider perceived academic quality when making school choice decisions (Glazerman & Dotter, 2017; Kleitz et al, 2000), evidence is also growing that nonacademic factors can influence school choice decisions as much as, if not more than, academic considerations (Billingham & Hunt, 2016; Garcia, 2008; Harris & Larsen, 2014; Jacobs, 2013; Ladd & Turaeva, 2020). In particular, many marginalized students—including students of color, linguistic or ethnic minority students, and LGBTQ+ students—and their families consider supportive social environments that reduce the risk of discrimination to be a top priority in their school choice decisions (Cooper, 2005; Fox & Buchanan, 2014; Posey-Maddox et al, 2021; Wilson, 2016).…”
Section: Theoretical Frameworkmentioning
confidence: 99%